A Unique Retrorectal Tumor With Neuroendocrine Differentiation: Case Report and Review of the Literature. (June 2013) - Misawa, Shun-ichi; Horie, Hisanaga; Yamaguchi, Takehiko; Kobayashi, Shigeru; Kumano, Hidetoshi; Lefor, Alan T.; Yasuda, Yoshikazu
Retrorectal or presacral tumors are very rare. We report a unique case of a retrorectal tumor with neuroendocrine differentiation, consisting of high- and low-grade components. A 53-year-old woman treated for a perianal abscess at another clinic was referred to our hospital for continued anal pain. Digital rectal examination identified a soft tumor with a smooth surface in the lower rectum. Pelvic computed tomography and magnetic resonance imaging detected a large cystic tumor measuring 8 cm in diameter in the retrorectal space of the pelvis. The border between the tumor and rectal wall, levator ani and vaginal wall was obscure. Fine-needle aspiration cytology was highly suggestive of carcinoma. Abdominoperineal resection was performed, and the tumor was histologically diagnosed as a neuroendocrine carcinoma based on immunohistochemical staining. No previous case has been reported with cystic growth of a neuroendocrine carcinoma in the retrorectal space.